Climate Models Don’t Give Us The Full Story (Orinoquia, 2008)
Titulo en español:Modelos del Clima nos han Dado la Historia ImcompletaRESUME:  In the debate about global warming we forget at our peril the role of ecosystems in giving us a climate we can live with. Life co-evolving with our planet over thousands of millions of years has created an envi- ronment apt for millions upon millions of species, from bacteria to the massive whale or towering red- wood trees. In its totality and working together through complex, even endogenous, symbiotic re- lationships, life gives us a relatively stable climate, modifying the amount of heat stored at the Earth’s surface, regulating the clouds that bring rain to the continents, and changing the colour of the Earth so that it differentially absorbs energy from the Sun or on the contrary, reflects it back into space.